Impact of containment and mitigation measures on children and youth with ASD during the COVID-19 pandemic: Report from the ELENA cohort. (May 2021) - Berard, Mathilde; Rattaz, Cécile; Peries, Marianne; Loubersac, Julie; Munir, Kerim; Baghdadli, Amaria
Abstract: Background: Containment, involving separation and restriction of movement of people due to the COVID-19 pandemic, and mitigation, also referred to as lockdown, involving closure of schools, universities and public venues, has had a profound impact on people's lives globally. The study focuses on the effects of containment and mitigation measures, on the behavior of children and youth (CaY) with Autism Spectrum Disorders (ASD). The study primary aim was to examine the impact of these urgent measures on the behaviors, communication, sleep, and nutritional status of the CaY. A secondary aim was to explore risk and protective factors on behavior change including sociodemographic variables, living conditions, ASD symptom severity and continuity of interventions. Methods: The study sample consisted of 239 ASD subjects, 2–21 years of age, enrolled in the ELENA cohort in France at Stage 3 confinement and mitigation measures announced on March 16, 2020. A parent informant completed the COVID-19 questionnaire. Results: Of the domains examined, challenging behaviors, communicative skills and sleep had the greatest impact; in terms of risk and protective factors, subject age, ASD severity, single parenthood, daily living skills, and intervention continuity were most likely to impact behaviors; living conditions were not linked to behavior change. Conclusions: The findings highlight the topography of behavioral change in CaY with ASD following institution of containment and mitigation measures during the COVID-19 pandemic and help identify risk and protective factors to help better address needs and tailor interventions in the future. Highlights: Large parental survey from a well-characterized cohort of children with ASD. Confinement due to COVID-19 pandemic involving both negative and positive effects. Worsening of sleep and challenging or stereotyped behaviors during confinement. Improvement of communication for one third of the children during confinement. Risk factors: older age, high autism severity, single parent family, interrupted specialized interventions.